AKTUALISASI NILAI-NILAI TASAMUH DALAM KEHIDUPAN POLITIK DI INDONESIA - Muh. Haras Rasyid (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2019)
Meaning of the title is to revive and apply the values ​​of tasamuh, as mutual respect between fellow elements of the Indonesian nation, both citizens and individuals, especially those who engage in politics. This article is inspired by the reality of politics that is widely occurring which involves not only interested parties in the political arena, but also ordinary people who are dragged into the political vortex. Likewise, not only on political issues that are the central theme, but also social and religious issues are polished and played from time to time make the intensity increases at the height of the political event. For this reason, the actualization of tasamuh as one of the ideal concept in political life, nation and religion is a necessary thing, to present in the midst of Indonesian society reducing heat of political tension.